Front Line Extremity and Orthopaedic Surgery A Practical Guide - Bone, Lawrence B.; Mamczak, Christiaan N.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book is designed as an easy to read reference and practical guide to the management of combat extremity injuries, which account for a high percentage of the injuries sustained in recent and current conflicts. The surgical techniques appropriate to the full range of extremity injuries and some other frequent injuries, such as trauma to the spine and pelvis, are clearly described with the aid of helpful illustrations. In each chapter a “bottom line up front” approach is adopted, providing key messages first; a further important feature is the emphasis placed on case-based information and lessons learned from practice. Care has been taken to ensure that the advice provided is straightforward and in line with military clinical practice guidelines.   This guide will be relevant to all physicians working in forward surgical teams, combat surgical hospitals, or the “Charlie Med”. The authors are without exception experienced surgeons who have been deployed to Iraq or Afghanistan at least once, and the editors are ideally suited to their task: Dr. Lawrence Bone has been an orthopaedic and general surgical trauma surgeon for more than 30 years and has had military training and experience in combat casualty care, while Dr. Christiaan Mamczak is an Attending Orthopaedic Trauma Surgeon in the United States Navy and has served as Head Orthopaedic Trauma Surgeon at a NATO Multinational Medical Unit in Afghanistan.
Pre-hospital and en-route care -- Combat triage and mass casualty management -- Initial management and priorities -- Damage control resuscitation – Blast injuries -- Foot and ankle injuries -- Tibia fractures -- B.K. amputations -- Vascular injuries of the lower extremity -- Use of fasciotomies of the lower extremity -- Distal femur fractures -- A.K. amputations -- Femur fractures -- Pelvic injuries and hip dislocations -- Hand injuries -- Arm and forearm Injuries -- Shoulder girdle injuries -- Upper extremity vascular injuries -- Spinal fractures -- Burns and extremity fractures.
Keywords: Orthopedics; Traumatology; Surgical Orthopedics; Traumatic Surgery